Spinal Cord Stimulation Attenuates Mechanical Allodynia and Increases Central Resolvin D1 Levels in Rats With Spared Nerve Injury - Tao, Xueshu; Luo, Xin; Zhang, Tianhe; Hershey, Brad; Esteller, Rosana; Ji, Ru-Rong (Frontiers in Physiology, 2021)
Mounting evidence from animal models of inflammatory and neuropathic pain suggests that inflammation regulates the resolution of pain by producing specialized pro-resolving mediators (SPMs), such as resolvin D1 (RvD1). However, it remains unclear how SPMs are induced in the central nervous system and whether these mechanisms can be reconciled with outcomes of neuromodulation therapies for pain, such as spinal cord stimulation. Here we show that in a male rat model of neuropathic pain produced by spared nerve injury (SNI), 1 kHz spinal cord stimulation (1 kHz SCS) alone was sufficient to reduce mechanical allodynia and increase RvD1 in the cerebrospinal fluid (CSF). SNI resulted in robust and persistent mechanical allodynia and cold allodynia. Spinal cord electrode implantation was conducted at the T11-T13 vertebral level one week after SNI. The spinal locations of the implanted electrodes were validated by X-Ray radiography. 1 kHz SCS was applied for 6 hours at 0.1 ms pulse-width. SCS alone effectively reduced nerve injury-induced mechanical allodynia during stimulation without affecting SNI-induced cold allodynia. SCS alone significantly reduced IL-1b levels in both serum and CSF samples. Strikingly, SCS significantly increased RvD1 levels in the CSF but not serum. Finally, intrathecal injection of RvD1 (100 and 500 ng, i.t.) 4 weeks after nerve injury reduced SNI-induced mechanical allodynia in a dose-dependent manner. Our findings suggest that 1 kHz SCS may alleviate neuropathic pain via reduction of IL-1b and via production and/or release of RvD1 to control SNI-induced neuroinflammation.